Season of conception and neurodevelopmental outcomes in singleton preterm infants less than 29 weeks gestation - Roychoudhury, Smita; Tang, Selphee; Hasan, Shabih U.; Fonseca, Kevin; Lodha, Abhay; Alshaikh, Belal; Alawad, Essa; Yusuf, Kamran (Frontiers in Pediatrics, 2025)
BackgroundEnvironmental factors vary with the seasons and affect fetal development. Our objective was to assess the impact of the season of conception on neurodevelopmental outcomes at 18–21 months corrected age in singleton infants <29 weeks’ gestation.MethodsA retrospective cohort study of infants born between 2006 and 2015 at a tertiary-level neonatal intensive care unit was conducted. The conception date was calculated as the date of birth minus gestational age plus 14 days, and the conception dates were then divided into winter and non-winter months. The primary outcomes were a composite score of <85 in any of the cognitive, language, or motor components of the Bayley Scales of Infant and Toddler Development, 3rd edition (Bayley-III), at 18–21 months corrected gestational age, and scores of <85 in the individual components. Multivariate logistic regression was used to assess confounders.ResultsOf the 493 eligible infants, 162 (32.8%) were conceived in winter. There was no difference in the adjusted odds ratios (aORs) of any Bayley-III cognitive, language, or motor composite scores of <85 between the two groups. The aORs of cognitive and language scores <85 in the winter group were significantly higher [2.78, 95% confidence interval (CI) 1.37–5.65 and 1.97, 95% CI 1.07–3.62, respectively].ConclusionSingleton infants <29 weeks’ gestation conceived in winter months have worse cognitive and language outcomes. Our results need validation in other and larger cohorts.